Ziemianie – prekursorzy przemysłu na wschodnich terenach dawnej Rzeczypospolitej w pierwszej połowie XIX w. - Naruszewicz, Edward; Naruszewicz, Karol (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Count Ludwik Pac, count Karol Brzostowski and princess Anna Jabłonowska are the progressive Polish magnates. Their activity as landowners was to modernize their own properties as well as the farmers’ ones. To realize these tasks very essential was well developed industry which help them. Not only the superiors found bread and living conditions. The magnates took part in organizing education. They knew that country inhabitants had waited for education very eagerly. Until today the work of the magnates has been respected by the people.